Exercise improves the social and behavioral skills of children and adolescent with autism spectrum disorders - Toscano, Chrystiane V. A.; Ferreira, José P.; Quinaud, Ricardo T.; Silva, Keity M. N.; Carvalho, Humberto M.; Gaspar, Joana M. (Frontiers in Psychiatry, 2022)
There is no standard treatment for Autism Spectrum Disorders (ASD), but there are many ways to minimize its symptoms and maximize functioning among children with ASD. As past research has suggested that exercise and other physical activities may be beneficial, this study examined the effects of physical activity on primary symptoms of and comorbidities associated with ASD. We allocated 229 children with ASD, ranging in age from 2.3 – 17.3 years (M = 7.8, SD = 3.2) into three groups: (a) exercise-intervention group, b) control group from the same institution, and (c) control group from another institution. We used Bayesian multilevel regression modeling to examine participant outcomes responses to the exercise intervention. Our results showed that exercise intervention substantially decreased ASD social interaction problems, attention deficit, emotional reactivity, stereotypical verbal and motor behavior, and sleep disturbances. We observed no exercise-based changes for eye contact and food selectivity, but eye contact, attention deficit, and sleep disturbance responses were influenced by the participants’ ASD severity and socioeconomic status. We conclude that children and adolescents with ASD exposed to an exercise intervention had an important improvement in ASD symptoms, highlighting that exercise programs can be a powerful complementary therapy for the ASD population.